2014
DOI: 10.1063/1.4881463
|View full text |Cite
|
Sign up to set email alerts
|

Observation of early shell-dopant mix in OMEGA direct-drive implosions and comparisons with radiation-hydrodynamic simulations

Abstract: Temporally, spatially, and spectrally resolved x-ray image data from direct-drive implosions on OMEGA were interpreted with the aid of radiation-hydrodynamic simulations. Neither clean calculations nor those using a turbulent mix model can explain fully the observed migration of shell-dopant material (titanium) into the core. Shell-dopant migration was observed via time-dependent, spatially integrated spectra, and spatially and spectrally resolved x-ray images of capsule implosions and resultant dopant emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Although direct comparisons of our LTE opacity calculations with the NIF measurements are not appropriate, we do find that our calculated line positions appear to be consistent with the measurements presented in [12] as well as the associated modeling presented in that work. ATOMIC has been used in non-LTE mode (including consideration of spatial gradients and radiation transport) to successfully compare with earlier NIF measurements [13] and Omega measurements [14]. We finally note that the positions of the Li-like, He-like, and H-like Kr line features shown in Figure 5 appear to be in excellent agreement with the NIST recommended data for these lines [33].…”
Section: Kr Opacitysupporting
confidence: 58%
See 1 more Smart Citation
“…Although direct comparisons of our LTE opacity calculations with the NIF measurements are not appropriate, we do find that our calculated line positions appear to be consistent with the measurements presented in [12] as well as the associated modeling presented in that work. ATOMIC has been used in non-LTE mode (including consideration of spatial gradients and radiation transport) to successfully compare with earlier NIF measurements [13] and Omega measurements [14]. We finally note that the positions of the Li-like, He-like, and H-like Kr line features shown in Figure 5 appear to be in excellent agreement with the NIST recommended data for these lines [33].…”
Section: Kr Opacitysupporting
confidence: 58%
“…Several short summaries of our new opacity tables for hydrogen through zinc have recently been published in various proceedings [10,11], and instead of repeating such summaries, we aim instead in this contribution to provide a short description of some recent work by us that attempts to calculate opacities for elements beyond zinc. Such extensions are motivated by the continuing importance of accurate opacities and radiation transport models to other plasma studies found in inertial confinement fusion (ICF) research (e.g., [12][13][14]), industrial plasmas [15], and in the field of magnetic confinement fusion. Some of these fields require models for elements that are not normally important in astrophysics research (such as Sn or W), and it is important to be able to provide accurate opacities for such systems.…”
Section: Introductionmentioning
confidence: 99%
“…To compare with the PDD implosion observations, Fig. 7 shows an image recorded in OMEGA shot 65036 where similar targets were driven with a spherically symmetric, 60-beam drive [31]. No "double-bun" structure was observed in these experiment along any LOS.…”
Section: X-ray Imaging Observations and Discussionmentioning
confidence: 99%
“…In an unstable implosion, a trace amount of shell material mixed into the hot spot can increase the x-ray emission measurably because of the relatively high emissivity per atom of carbon (or other shell materials) without significantly altering the DT concentration and the hot-spot conditions [14]. Consequently, measured hot-spot conditions and mixing mass were measured in both NIF and OMEGA implosions, based on the K-shell line emission of M-shell ionization species of higher-Z shell dopants [15][16][17]. Dopant line emission indicates mix originating from the doped shell layers only, while carbon continuum emission indicates fuel-shell mix originating from anywhere in the capsule shell.…”
Section: Introductionmentioning
confidence: 99%